Emphasizing the losses or the gains: comparing situational and individual moderators of framed messages to promote fruit and vegetable intake - Godinho, C. A. (2017)
Health messages are a commonly used way to promote changes in dietary habits but their efficacy could be enhanced by strategies such as the way in which the presented arguments are framed. This study aimed to test the effectiveness of framed messages (gain vs. loss) on behavioural intention and fruit and vegetable (FV) intake, comparing predictions based on prominent theoretical perspectives on message framing (function of the health behaviour and recipients' motivational orientation) and by further exploring the role of baseline intentions as a potential moderator of the framing effects. Undergraduate students (N = 180) completed the three assessment points in time. At baseline, individual moderators (motivational orientation and intentions) and fruit and vegetable intake were assessed. One week later, participants were randomly assigned to the loss or gain-framed message and indicated their intentions for FV intake the following week. A week later, FV intake over the previous week was assessed. The gain-frame was not conducive, per se, to higher intentions or behaviour. Having intention as the outcome, only baseline intentions moderated the effects of message frame. When considering FV intake as the outcome, both motivational orientation and baseline intentions moderated the effects of message frame, with the loss-frame promoting higher FV intake among individuals who were prevention-oriented and had higher baseline intentions. Findings suggest that the success of framed messages for FV intake depends upon the recipient's characteristics, such as motivational orientation, baseline intentions, and cultural background, with implications for health communication interventions.